Measuring soccer skill performance: a review - Ali, A. (Scandinavian Journal of Medicine & Science in Sports, 2011)
The ability to execute skilled movement patterns efficiently and effectively is the most important aspect of soccer performance and players must apply cognitive, perceptual and motor skills to rapidly changing situations. There have been attempts to measure these parameters for talent identification (or development) purposes and skill acquisition and intervention research; the aim of this review is to examine the strengths and limitations of these tests. High levels of perceptual and cognitive skill are characteristics of those players who are able look in the right places for information and process this information efficiently before deciding on a suitable course of action. The motor skills required to successfully control, pass, dribble and shoot the ball at goal are fundamental skills of the soccer player and a variety of methods have been used to measure these aspects. The tests mentioned in this review vary in their complexity and the type of skill(s) they purport to measure. The assessment of choice must come down to a number of factors including cost, available time and space, number of athletes in the cohort and experience of researchers. Furthermore, consideration must be given to the aim(s) of the research/assessment and issues relating to validity and reliability.